2012
DOI: 10.1016/j.schres.2012.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Language processing abnormalities in adolescents with psychotic-like experiences: An event related potential study

Abstract: Language impairments are a well established finding in patients with schizophrenia and in individuals at-risk for psychosis. A growing body of research has revealed shared risk factors between individuals with psychotic-like experiences (PLEs) from the general population and patients with schizophrenia. In particular, adolescents with PLEs have been shown to be at an increased risk for later psychosis. However, to date there has been little information published on electrophysiological correlates of language c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 45 publications
(43 reference statements)
2
7
0
Order By: Relevance
“…Previous research by Murphy et al [63] found reduced amplitude of the P300 component in a group of adolescents who reported psychotic symptoms compared to a control group on a receptive language task. Individuals with psychotic symptoms were characterised by reduced accuracy and smaller P300 amplitude on a computerised version of the British Picture Vocabulary Scale [64].…”
Section: Discussionmentioning
confidence: 92%
“…Previous research by Murphy et al [63] found reduced amplitude of the P300 component in a group of adolescents who reported psychotic symptoms compared to a control group on a receptive language task. Individuals with psychotic symptoms were characterised by reduced accuracy and smaller P300 amplitude on a computerised version of the British Picture Vocabulary Scale [64].…”
Section: Discussionmentioning
confidence: 92%
“…preadolescents with psychotic-like experiences with matched healthy controls, an initial set of experiments showed functional changes encompassing the error-related processing network, 83 the perspective-taking network, 84 and the status of intrinsic functional connectivity within the inhibitory control network, 85 in line with behavioral findings previously mentioned (see “ToM in Children With Hallucinations” section). Such differences measured in the blood-oxygen-level-dependent (BOLD) signal—during cognitive tasks and at rest—were shown to be associated with gray matter 83,86 and event-related potentials changes 87 in at-risk or first-episode adolescents compared with controls, supporting a hypothesis of distributed neural impairments associated with the psychosis phenotype in general.…”
Section: Cognitive Theories Of Hallucinations In Children and Adolescmentioning
confidence: 91%
“…Furthermore, neural generators of the MMN have been located in the IFG (66). The P3 might be related to domains involved in language processing as well (78). At least, an intertwining of the P3 with dysfunctions of language comprehension has been found in subjects displaying psychotic-like experiences (78).…”
Section: Discussionmentioning
confidence: 99%
“…The P3 might be related to domains involved in language processing as well (78). At least, an intertwining of the P3 with dysfunctions of language comprehension has been found in subjects displaying psychotic-like experiences (78). Taken together, it can be hypothesized that the language related BS may be mirrored by particular EEG disturbances that relate to language processing domains, which have been found aberrantly activated in fMRI investigations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation